(untitled) (Revista de Ciências Agroveterinárias, 2023)
Phosphate fertilization of cassava cultivars leads to increased production costs that may be economically viable depending on the quantity used and the corresponding productivity. In this sense, the objective of the work was to analyse the economic viability of the irrigated cultivation of table cassava cultivars in response to the application of phosphorus doses in the Brazilian semiarid region. Two agricultural crops were conducted at the Experimental Farm Rafael Fernandes, Mossoró, RN, from June 2018 to April 2019 and from June 2019 to April 2020. The experimental design was in randomized blocks arranged in subdivided plots, with four replications. The doses of phosphorus (0, 60, 120, 180, and 240 kg ha-1 of P2O5) were applied to the plots and the table cassava cultivars (Água Morna, BRS Gema de Ovo, Recife and Venâncio) arranged in the subplots. The total costs for one hectare of cultivation were estimated and the gross income, net income, rate of return, and profitability index were calculated. The use of phosphate fertilizer was economically viable for the cassava cultivars studied in the two crops. The cultivars Água Morna, BRS Gema de Ovo, and Recife are the best cultivation options for the semiarid region of Rio Grande do Norteas they give high yields with the highest profitability. The Recife cultivar was the region’s most profitable cultivation, with a profit ranging from R 40,331.07 ha-1 to R 57,603.46 ha-1 in both seasons, with an average recommendation of 120 kg ha-1 of P2O5.